Analysis of Prospective Physics Teacher's Misconceptions on Interference Material using Certainty of Response Index (CRI) - Andhiani Eka Kusumawati; Wulan Anggraini; Bayu Setiaji (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The purpose of this research is to find out the occurrence of misconceptions in students regarding the concept of light interference and to find out the causes of these misconceptions. The research was conducted in the form of a three-tier multiple-choice test and analyzed using the Certain of Response Index (CRI) method which will be a benchmark in the level of confidence in answering a question. The research was conducted on 21 undergraduate students of UNY Physics with light interference material. From this study, it was shown that the level of conceptual understanding of undergraduate students in Physics at UNY on light interference was included in the category of not understanding concepts at 46.91%, understanding concepts at 36.12%, and misconceptions at 17.07%. The results of the level of misconceptions obtained are low. This is caused by a conceptual error that is owned by students and the application of concepts that do not match the statements given.